2016
DOI: 10.4103/0366-6999.184457
|View full text |Cite
|
Sign up to set email alerts
|

Frontolateral Approach Applied to Sellar Region Lesions

Abstract: Background:Various surgical approaches for the removal of sellar region lesions have previously been described. This study aimed to evaluate the reliability and safety of the frontolateral approach (FLA) to remove sellar region lesions.Methods:We presented a retrospective study of 79 patients with sellar region lesions who were admitted and operated by the FLA approach from August 2011 to August 2015 in Department of Neurosurgery of Beijing Tian Tan Hospital. We classified FLA into three types, compared the FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[ 26 ] The primary therapeutic approach is neurosurgery. [ 4 27 ] If surgery is contraindicated or declined, radiotherapy might be an option. Medically, SST analogs can control hormone hypersecretion for 90% of patients; long-time therapy should cause significant tumor shrinkage for about 45% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] The primary therapeutic approach is neurosurgery. [ 4 27 ] If surgery is contraindicated or declined, radiotherapy might be an option. Medically, SST analogs can control hormone hypersecretion for 90% of patients; long-time therapy should cause significant tumor shrinkage for about 45% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study on sellar suprasellar lesions operated transcranially via pterional approach reported transient Diabetes Mellitus in 23.4%, meningitis in 13%, panhypopituitarism in 6.3, and CSF leak in 4.2% of cases. 11 The literature review had shown many complications, including transient and permanent diabetes mellitus, CSF leak, Worsening of a visual deficit, temporary motor deficit, transient third nerve palsy, intracerebral hematoma, hydrocephalus, infection of CNS, Vasopasm and tearing of anterior circulation arteries, cavernous sinus injury, and panhypopituitarism, etc. in patients undergoing surgical resection for the sellar suprasellar lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the major challenges for neurosurgery is how to achieve the maximal resection of tumors and few postoperative complications. [ 1 5 ] Different surgical approaches may be used according to different growth directions of sellar region tumors, including frontolateral approach, [ 6 ] endoscopic endonasal approach, [ 7 ] and endoscopic endonasal transspehenoidal approach. [ 8 ] Anterior interhemispheric approach can achieve resection of a variety of large tumors located along the median line of the sellar region by separating the median line structure of the frontal part exposed in the sellar region in a interhemispheric fissure manner.…”
Section: Introductionmentioning
confidence: 99%